Peningkatan Peran Perempuan Bagi Pendapatan Keluarga Pada Industri Tempe di Desa Pliken Kecamatan Kembaran Kabupaten Banyumas - Ratna Setyawati Gunawan; Barokatuminalloh Barokatuminalloh (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2006)
This research was aimed to analyze the economy contribution from woman workers to their family income, and the influence of work hours, age and family burden to their income. This research was also to find out the development strategy for woman workers in micro and small industry area, especially in Pliken Village. The result first, the income from woman workers give large contribution to their family income. Their income is needed to affix their husband income. In fact, there are many woman workers who have higher income. So it can be conclude that their income is more dominant to fulfill their family needs than their husband income.Work hours, age and family burden have influence to the family income. Work hours and age have positive influence, while family burden has negative influence. Work hours variable is the most influential variable to income. The low income is caused by short work hours. It is only 2 – 3 hours a day. It is find out also that the moulded soya bean industry is relative near with the city. It will make easier in marketing term. But, caused of its small scale business, the business cannot get the sufficient credit access.Key words: economy contribution, income and small scale moulded soya bean industry